PERENCANAAN PARTISIPATIF DALAM PEMBANGUNAN LOKAL: STUDI DI KOTA BANDUNG - Idil Akbar (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2018)
Participatory planning supports community to involve in government and regional development. This community effort is one of the important manifestations of good governance and democracy. The importance of participatory planning in optimizing community participation and its implementation in regional development is an important topic in this article. Participatory planning emphasizes the importance of broad participation for every community, both individually and in groups, from planning to decision making. A development with a welfare goal cannot be ascertained its achievement without community participation.